Pharmacological Interventions for Cirrhotic Ascites: From Challenges to Emerging Therapeutic Horizons - Yuan Gao; Xin Liu; Yunyi Gao; Meili Duan; Bing Hou; Yu Chen (Gut and Liver)
Ascites is the most common complication in patients with decompensated cirrhosis. This condition results in a severely impaired quality of life, excessive healthcare use, recurrent hospitalizations and significant morbidity and mortality. While loop diuretics and mineralocorticoid receptor antagonists are commonly employed for symptom relief, our understanding of their impact on survival remains limited. A comprehensive understanding of the underlying pathophysiological mechanism of ascites is crucial for its optimal management. The renin-angiotensin-aldosterone system (RAAS) is increasingly believed to play a pivotal role in the formation of cirrhotic ascites, as RAAS overactivation leads to a reduction in urine sodium excretion then a decrease in the ability of the kidneys to excrete water. In this review, the authors provide an overview of the pathogenesis of cirrhotic ascites, the challenges associated with current pharmacologic treatments, and the previous attempts to modulate the RAAS, followed by a description of some emerging targeted RAAS agents with the potential to be used to treat ascites.